Sustainable product design and development - Desai, Anoop; Mital, Anil (Boca Raton, FL : CRC Press, 2021)
"This book outlines the process of sustainable product design and development. Design guidelines that contribute to prolonging the life of a product and minimizing its environmental impact are presented. Specifically, these guidelines enable product design for particular end of life (EOL) objectives such as reuse, recycling and remanufacturing. The book also presents mathematical models that would help the designer determine the cost of designing sustainable products. This cost can be computed early during the design stage of a product. The book presents different ways and means by which a product can address all three pillars of sustainability, i.e.: environmental conservation, social sustainability and economic sustainability. Various case studies are incorporated in different chapters as deemed appropriate. Case studies on designing products for assembly, disassembly and remanufacturing have been presented in respective chapters. The book also provides an overview of global environmental legislations to help the reader grasp the importance of waste management and sustainable product design. This book will be of interest to professionals, engineering students, environmental scientists and those in the business environment"--
Environmental legislations -- Design for disassembly -- Design for assembly -- Design for maintenance -- Consideration of reuse, recycling and remanufacturing -- Costing for sustainable product design.
OCLC-licensed vendor bibliographic record.
Keywords: Product design -- Environmental aspects; Sustainable design; TECHNOLOGY / Manufacturing